INSTITUTE OF SCIENCE OF UKRAINIAN SOCIETY: CULTURAL MEASURES OF MODERNIZATION (TO THE 100TH ANNIVERSARY OF THE ACADEMY OF SCIENCE OF UKRAINE) - Petrykova, Valentyna (Київський національний університет імені Тараса Шевченка, 2019)
The author investigates the organizational measures of modern Ukrainian society on the way of forming an effective system of science in accordance with the requirements of civilization development. Chronological boundaries of the study - the beginning of the nineteenth century until the present. The methodological basis for the study is the theoretical concept of the cyclical development of historical phenomena in relation to the world and local cultural spaces. The research is aimed at the cultural view of the modern problem of the modernization of the institute of science within the historically formed educational and scientific spaces of Ukraine. Taking a public view of the functioning of science in society for Ukraine is to identify it organizationally with the National Academy of Sciences of Ukraine. The Ukrainian Academy of Sciences (UAN) was founded on November 1, 1918. The Commission was responsible for the rationale for the creation of the Academy to draft a bill on the founding of the Academy of Sciences in Kyiv. The Commission included representatives of the Ukrainian scientific elite of that time, led by V.I. Vernadsky. The main functions of the UAN were the organization and coordination of the scientific forces of the state. The history of the development of the UAN testifies to the civilization content of the strategy for the development of national science for the entire period of the twentieth century. The beginning of the XXI century declared a new system of relations in the world society. The meaningfulness of such relationships is marked by a new post-industrial society. For Ukraine, the reform of the institute of science after world shifts is becoming urgent. The modern scientific space of Ukraine can be characterized as functioning of the coordinate system "universityacademy". An appeal to the principles of scientific democracy should ensure a balance between the development of science in the university sector and academic institutions. The financial self-determination of universities has an opportunity to actualize scientific research. The University is able today to ensure the development of the humanitarian component of science, which reproduces the traditions of national culture. The academic structure needs to reload the strategy for reforming the material and technical support of research work for the branches of science, which have high ratings in the countries of the world.

У статті проаналізовано проблему організаційного удосконалення наукового простору України. Характерним для історії наукового світу є визначення головних організаційних центрів дослідницької праці. Такими центрами стали університети та академії. Сформульовано гіпотезу сучасної модернізації інституту науки України за вимогами цивілізаційного зрушення суспільства ХХІ століття. Новий тип відносин постіндустріального суспільства вимагає мобільності у вирішенні проблеми ефективної організації науки в українському соціумі. Циклічний характер розвитку та зміни явищ культури, дає підстави визначити лідерами наукового знання сучасні університети. Окреслено історичні періоди розвитку університетів в Україні. Подано аргументи щодо важливості заснування Національної Академії наук у 1918 році як організаційного та координаційного центру. Визначено функціональні обов’язки УАН у справі організації науки в новоутвореній державі. Підкреслено цивілізаційний підхід до справи функціонування УАН у освітянському та науковому просторі 1920-х років. Окремо висвітлено факти еволюції сучасних університетів у якості лідерів координатної системи «університет - академія» для України. Акцентовано увагу на важливості розвитку гуманітарної науки для визначення національно-особливого у науковому просторі. Наведені факти історичного контексту відносно еволюції поняття «наука» у слов’янській писемності. Досліджено організаційні заходи сучасного українського суспільства на шляху формування ефективної системи науки. Хронологічні межі дослідження - початок ХІХ століття до сьогодення. Дослідження спрямовано на культурологічне бачення сучасної проблеми модернізації інституту науки в межах історично сформованого для України освітянського та наукового просторів.
ІНСТИТУТ НАУКИ УКРАЇНСЬКОГО СУСПІЛЬСТВА: КУЛЬТУРОЛОГІЧНІ ВИМІРИ МОДЕРНІЗАЦІЇ (ДО СТОРІЧЧЯ НАЦІОНАЛЬНОЇ АКАДЕМІЇ НАУК УКРАЇНИ)
Keywords: Academy of Sciences; intellectual history; classical university; scientific space; post modernization; national cultural tradition; Академія наук; інтелектуальна історія; класичний університет; науковий простір; постмодернізація; національна культурна традиція